Estimating selectivity of experimental diamond (T0) and turned mesh (T90) codends in multi-species Mediterranean bottom trawl - PETETTA, ANDREA; HERRMANN, BENT; VIRGILI, MASSIMO; De MARCO, ROCCO; CANDUCI, GIOVANNI; Li VELI, DANIEL; BARGIONE, GIADA; VASAPOLLO, CLAUDIO; LUCCHETTI, ALESSANDRO (Mediterranean Marine Science, 2020)
This paper evaluates the effect of changing from a diamond mesh codend (T0) to a 90° turned mesh codend (T90) on the size selectivity of seven commercially important species in the Mediterranean bottom trawl fishery. In sea trials conducted in the north-western Adriatic, two experimental codends made of 54 mm nominal mesh size netting and differing only in mesh configuration were alternately mounted on the same trawl. Overall, the T90 mesh significantly improved codend size selection for all the species analysed. The difference in the predicted average L50 values between the T90 and T0 codend was particularly marked in European hake (Merluccius merluccius, 21.26 vs 11.26 cm total length), common squid (Loligo vulgaris, 12.06 vs 7.88 cm mantle length) and mantis shrimp (Squilla mantis, 20.78 vs 13.35 mm carapace length). Both codends showed an excessive size selectivity, which involves a commercial loss, especially for red mullet (Mullus barbatus), Mediterranean horse mackerel (Trachurus mediterraneus) and whiting (Merlangius merlangus). These findings demonstrate the efficiency of the T90 configuration in excluding undersized specimens, especially of hake, whose average L50 was above the minimum conservation reference size of 20 cm. The adoption of this practical and inexpensive solution can contribute to improve the management of the demersal resources targeted by the Mediterranean bottom trawl fishery.